miR-125b/NRF2/HO-1 axis is involved in protection against oxidative stress of cystic fibrosis: A pilot study - Pelullo, Maria (Exp Ther Med, 2021)
In the physiopathology of cystic fibrosis (CF), oxidative stress implications are recognized and widely accepted. The cystic fibrosis transmembrane conductance regulator (CFTR) defects disrupt the intracellular redox balance causing CF pathological hallmarks. Therefore, oxidative stress together with aberrant expression levels of detoxification genes and microRNAs (miRNAs/miRs) may be associated with clinical outcome. Using total RNA extracted from epithelial nasal cells, the present study analyzed the expression levels of oxidative stress genes and one miRNA using quantitative PCR in a representative number of patients with CF compared with in healthy individuals. The present pilot study revealed the existence of an association among CFTR, genes involved in the oxidative stress response and miR-125b. The observed downregulation of CFTR gene expression was accompanied by increased expression levels of Nuclear factor erythroid derived-2 like2 and its targets NAD(P)H:Quinone Oxidoreductase and glutathione S-transferase 1. Moreover, the expression levels of heme oxygenase-1 (HO-1) and miR-125b were positively correlated with a forced expiratory volume in 1 sec (FEV1) >60% in patients with CF with chronic Pseudomonas aeruginosa lung infection (r=0.74; P<0.001 and r=0.57; P<0.001, respectively). The present study revealed the activation of an inducible, but not fully functional, oxidative stress response to protect airway cells against reactive oxygen species-dependent injury in CF disease. Additionally, the correlations of HO-1 and miR-125b expression with an improved FEV1 value suggested that these factors may synergistically protect the airway cells from oxidative stress damage, inflammation and apoptosis. Furthermore, HO-1 and miR-125b may be used as prognostic markers explaining the wide CF phenotypic variability as an additional control level over the CFTR gene mutations.